PROBLEMATIK PERKAWINAN ADAT PASU-PASU RAJA DI KECAMATAN AJIBATA KABUPATEN TOBA - Putri Artama (Jurnal Profil Hukum, 2025)
This research aims to understand and analyze the problems that arise as a result of the Pasu- pasu Raja marriage in the context of law and custom. The research medhod used of normative juridical, with the main data source being Law Number 1 of 1974 concerning marriage which is complemented by field research using observation techniques, namely by taking a distance from the research object. The results of the research show that the Pasu- pasu Raja traditional marriage is recognized according to custom but does not meet the legal requirements according Law Number 1 of 1974 concerning marriage which requires religious recognition and registration in the civil registry. As a result, couples who marry through Pasu-pasu Raja do not have a clear legal status which impacts their rights and obligations and children born in this marriage are considered illegitimate in the context of state law.